PENGARUH PEMBERIAN PUPUK KCl TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN OKRA (Abelmoschus esculentus L.) PADA MEDIA TANAM CAMPURAN KOMPOS KULIT KAKAO - Salwa Nurul Saqina; Dedi Kurniawan; Ahmad Nadhira (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2023)
Introduction: The purpose of this study was to determine the effect of the growth and production of okra plants on the application od KCl and planting media mixed with cocoa husk compost. Materials and Methods: This 'research' was carried out in October 2022-February 2023 on Jln Yos Sudarso hamlet 3, Suka Makmur village, Binjai district. This study used a factorial randomized block design (RBD) with 2 treatment factors. The first factor is the planting medium mixed with cocoa shell compost with the symbol (T) which consists of 3 treatment levels, namely: T0= Top soil, T1= Top soil + Cocoa husk compost (1: ½), T2= Top soil+Cocoa husk compost (1:1). The second factor was giving KCl fertilizer with the symbol (K) which consisted of 4 treatment levels, namely: K0= 0 gram/plant, K1= 5 gram/plant, K2= 10 gram/plant, K3= 15 gram/plant. Results: The results showed that the treatment of cocoa shell compost had a significant effect on stem diameter at 4 MST and flowering age, and had a very significant effect on plant height at 6 MST, 8 MST and 10 MST, number of leaves at 4 MST, 6 MST, 8 MST and 10 MST. MST, stem diameter at 6 MST, 8 MST and 10 MST, number of fruit planted, fruit weight planted, number of fruit per plot and fruit weight per plot. The application of KCl fertilizer had no significant effect on all parameters. Interaction of the two had a significant effect on the number of leaves aged 4 WAP.